Nonperforming loans in Malaysia's commercial banks: does economic growth matters? / Normah Erra Zulkifli and Zuriyati Ahmad - Zulkifli, Normah Erra; Ahmad, Zuriyati (Universiti Teknologi MARA, Selangor, 2022)
A loan is one of the primary sources of income earned by the banks and either directly or indirectly contributes to the country's economic growth. Previous studies have shown that economic growth can affect the number of loans given and the changes in nonperforming loans in the banking sector. During the economic downturn, the amount of nonperforming loans tends to increase. Most borrowers were unable to settle down their loans because some businesses went insolvent and left the loans unpaid. Therefore, this paper investigates the impact of economic growth on non-performing loans in Malaysia. Seven commercial banks are selected to be used in the panel data regression, with the data spanning from 1995 to 2020. The result from the fixedeffect model indicates that the changes in economic growth are positively related to nonperforming loans. However, the impact of economic growth does not significantly influence the changes in nonperforming loans in Malaysian commercial banks. While findings also reveal that return on asset, financial crisis and unemployment rate has a significant relationship with the nonperforming loans, with the magnitude of variables being as expected.